Neoliberalism and the Emergence of Private Sustainability Initiatives: The Case of the Brazilian Cattle Value Chain. (7th February 2018) - Guéneau, Stéphane
Abstract: Recent studies have examined the political significance of the emergence of governmental initiatives to develop sustainability standards for agricultural commodities in the transition economies. Yet, few studies have examined how neoliberal ideas influence the governance of value chains in the agri‐food sector of these countries. This paper's goal is to explore the changing role of the state in sustainable cattle value chain governance in Brazil, through a methodology of participant observation of the Brazilian Roundtable on Sustainable Livestock (GTPS). The results describe the technologies used to govern the cattle value chain, which involves a private action controlled at a distance by the state that is aimed at making products acceptable on world markets. This neoliberal governmentality does not address some crucial sustainability issues of the cattle value chain. The findings call for an extension of evaluation methods so that more attention can be devoted to alternative cattle production systems. Copyright © 2018 John Wiley & Sons, Ltd and ERP Environment